VALIDITAS DAN KEPRAKTISAN ISI BUKU ENSIKLOPEDIA FAMILI SAPINDACEAE KEBUN RAYA BANUA UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Diah Dwi Kurniawati; Muhammad Zaini; Kaspul Kaspul (Bioedukasi Jurnal Pendidikan Biologi, 2024)
Critical thinking skills in the 21st century need to be developed including the ability to evaluate, analyze, and use information to solve real-world problems. To put these skills into practice, a tool enriched with practical information based on experience has been created in the form of an encyclopedia, supported by various aspects of critical thinking in an encyclopedia book. This is a book containing information about all sciences in the form of a series of articles arranged alphabetically by title. The purpose of this study was to determine the relevance and practicality of the contents of the Sapindaceae Encyclopedia of the Banua Botanical Gardens. This study focuses on the development of assessments using the Educational Design Research (EDR) model using Tessmer's formative design. Research has found that the validity of this encyclopedia falls into the category of "good" as it contains content that teachers and students can use and the systematic structure of the encyclopedia is excellent. Content practice evaluation results are classified in the "good" category because they contain content that is suitable for subject activities, the structure of the book is interesting and easy to understand, and they can train students' critical thinking skills.Â